DNA Methylation and Chromatin Regulation during Fleshy Fruit Development and Ripening - Gallusci, Philippe; Hodgman, Charlie; Teyssier, Emeline; Seymour, Graham B. (Frontiers in Plant Science, 2016)
Fruit ripening is a developmental process that results in the leaf-like carpel organ of the flower becoming a mature ovary primed for dispersal of the seeds. Ripening in fleshy fruits involves a profound metabolic phase change that until recently was known to be only under strict hormonal and genetic control. This work reviews recent developments in our understanding of the epigenetic regulation of fruit ripening. We start by describing the current state of the art about processes involved in histone post translational modification (PTM) and the remodeling of chromatin structure and their impact on ripening. However, the focus of this review is the impact of changes in DNA methylation levels on the expression of ripening-related genes. This includes those changes that result in heritable phenotypic variation in the absence of DNA sequence alterations, and the mechanisms for their initiation and maintenance. The majority of the studies described in the literature involve work on tomato, but evidence is emerging that ripening in other fruit species may also be under epigenetic control. We discuss how epigenetic differences may provide new targets for breeding and crop improvement.